'Julius Nyerere': The man, the word, and the order of discourse - (:unkn) unknown (My University, 2016)
The British historian Anthony Kirk-Greene from Oxford University once worried that undertaking a new publication about African heads of state may risk déjà vu (Kirk-Greene, 1991). In the 1980s, an influential literature reflected upon leadership, personal rule and national trajectories in Africa. It adopted a comparative and typological approach that resorted to a corpus of earlier scholarly studies in political history published from the mid-1960s to the late 1970s (Jackson and Rosberg, 1982; Cartwright, 1983). Did the first generation of postcolonial political leaders belong to the category of prince, autocrat, prophets or tyrant? Should “His Eternity”, “His Eccentricity”, or “His Exemplarity” (Kirk-Greene, 1991) rather be seen as modern Janus, both prince and autocrat, or philosopher and tyrannical king, like Jomo Kenyatta in Kenya or Sékou Touré in Guinea? Biographies of the most renowned leaders – most of the time the Founding Fathers of the fledgling Sub-Saharan African nation-states – added to these debates about the personal power and styles of leadership in order to engage with the question of the foundations of legitimacy of the early postcolonial political regimes in Africa.
Keywords: African Research